Electrical and thermal properties of K x Cu 2−x S superionic alloys - Кутербеков К. A.; Кабышев, А. М.; Бекмырза , К.; Балапанов , М.; Кубенова, М.М.; Палымбетов , Р.; Сахабаева , С.; Куланова, К. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
The paper presents and discusses the results of phase analysis and experimental studies of electronic conductivity and thermo-electromotive force, the thermal conductivity coefficient of K x Cu 2−x S alloy samples (x=0.1, 0.2, 0.25) in the temperature range from 30 to 420 ◦ C. According to the results of x-ray phase analysis, the alloys are a mixture of different phases of copper sulfide: cubic Fm-3m phase Cu 1.84 S, cubic Fm-3m phase Cu 2 S, rhombohedral R-3m phase Cu 17 S 9 and metastable tetragonal P4 3 2 1 2 phase Cu 2 S. Differential scanning thermometry showed an endothermic peak extending from 84 to 102 ◦ C caused by phase transitions from the rhombohedral and tetragonal phases to the hexagonal phase of copper sulfide. For the composition of K 0.2 Cu 1.8 S above 300 ◦ C, a strong increase in the thermo-EMF coefficient (up to 4 mV/K) and a decrease in thermal conductivity (from 0.87 to 0.4 W/m·K) were observed, resulting in a very high peak value of the dimensionless thermoelectric efficiency ZT=3.5 at 380 ◦ C.